Migrasomes derived from human umbilical cord mesenchymal stem cells: a new therapeutic agent for ovalbumin-induced asthma in mice - Weifeng Gu; Tingting Zheng; Wen Li; Xinkai Luo; Xiaowei Xu; Ying Wang; Chaoming Mao; Yongbin Ma; Liyang Dong (Stem Cell Research & Therapy)
Abstract Background Asthma is a prevalent respiratory disease, and its management remains largely unsatisfactory. Mesenchymal stem cells (MSCs) have been demonstrated to be efficacious in reducing airway inflammation in experimental allergic diseases, representing a potential alternative treatment for asthma. Migrasomes are recently identified extracellular vesicles (EVs) generated in migrating cells and facilitate intercellular communication. The objective of this study was to investigate the therapeutic effects of migrasomes obtained from MSC in a model of asthma. Methods Migrasomes produced by human umbilical cord MSCs (hUCMSCs) were isolated by sequential centrifugation. Characterization of hUCMSC-derived migrasomes were carried out by transmission electron microscopy and western blot analysis. The therapeutic effects of migrasomes on airway inflammation in ovalbumin (OVA)-induced asthmatic mice were evaluated by hematoxylin-eosin (HE) and periodic-acid schiff (PAS) staining, and their mechanism were further testified by immunofluorescent staining, real-time PCR and flow cytometry. Results Here, we showed that inhibition of migrasomes’ production dramatically impaired the anti-inflammatory effects of hUCMSCs in OVA animals, as evidenced by a notable increase in both the infiltration of inflammatory cells and the number of epithelial goblet cells. We successfully isolated hUCMSC-migrasomes, which were morphologically intact and positive for the specific migrasomes markers. The administration of hUCMSC-migrasomes was observed to significantly ameliorate the symptoms of airway inflammation and mucus production in asthmatic mice. Additionally, the expression of Th2 cytokines (IL-4, IL-5 and IL-13) were found to be reduced, while the activation of dendritic cells (DCs) was inhibited. HUCMSC-migrasomes could possibly be delivered to lung region after injection, and were able to be taken in by DCs both in vivo and in vitro. Notably, in vitro, migraosmes decreased the capacity of BMDCs to stimulate OVA-specific Th2-cell responses. More importantly, we found that adoptive transfer of hUCMSC-migrasomes-treated BMDCs was sufficient to protect mice from allergic airway inflammation. In addition, we found that hUCMSC-migrasomes inhibited the receptor for advanced glycation end-products (RAGE) signal in OVA-treated BMDCs in vitro and in asthma mice lung in vivo. Conclusion Our results provided the first evidence that hUCMSC-migrasomes possess anti-inflammatory properties in OVA-induced allergic mice, which may provide a novel “MSC-cell free” therapeutic agent for the management of asthma.